Answer:
D) {11,-4,-29}
Step-by-step explanation:
rewrite the equation as y= -5x+1 and plug in -2,1 and 6 to get y
-5*-2+1=11
-5*1+1=-4
-5*6+1=-29
The answer is -14
Explanation:
x - 8 = 2x + 6
We move all term to the left
x - 8 - ( 2x + 6 ) = 0
We get rid of parentheses
x - 2x - 6 - 8 = 0
We add all the numbers together, and all the variables
-1x - 14 = 0
We move all terms containing x to the left, all other term to the right
-x = 14
x = 14/-1
x = -14
Answer:
A. It Increases
Step-by-step explanation:
Given the expression:
1+3f
When f=1, 1+3f=1+3(1)=1+3=4
When f=2, 1+3f=1+3(2)=1+6=7
When f=3, 1+3f=1+3(3)=1+9=10
We can see that the value of the given expression for each successive term increases and in fact form the sequence
4,7,10,...
Therefore, when f increases, 1+3f increases.
Answer:
Manager will get $40
Step-by-step explanation:
2400*(1/12)=200, so Dylan made $200
200*(1/5)=40, so the manager made $40
Answer:
y
=
2
x
2
+
8
x
+
17
Step-by-step explanation: